Petrol monitoring system in storage tank - Muhammad Taufiq, Mohd Safwan Chin (2014)
Petrol Monitoring System in Storage Tank (PMSST) is developed to facilitate manager and staff of Trident Bliss Sdn. Bhd. This system can help and easily the manager, supervisor and staff to monitor the petrol level remain in the storage tank at petrol station. In the existing system, process of collecting volume of petrol level in storage tank is conducted manually by using fuel tank dipstick. The processes call dipping. Therefore, the proposed system is to change the current process to computerized system that connected to ultrasonic censor. The methodology that has been applied in the project development is the Prototype model. The advantage of prototype model is it can be early act or representation of the final product and this method can reduce risk and limit expenses and costs. In the development of PMSST, Visual Studio 2010 and Microsoft access 2010 has been used as programming tools while Arduino Uno R3 with Ultrasonic Module HC-SR04 Distance Measuring as hardware tools. Visual Studio has become one of the world’s most widely used programming languages while Microsoft access 2010 is an open source relational database management system. Arduino Uno R3 is an open-source physical computing platform based on a simple i/o board and development that implements the processing/wiring language Ultrasonic Module HC-SR04 Distance Measuring provide noncontact measurement function includes ultrasonic transmitters, receiver and control circuit. As a result, form system is developed and this system helps to simplify and efficiently used of monitoring remaining petrol activity.